Learning Motivation as A Factor Related to Students' Learning Independence of Class XI at SMK N 1 Kecamatan Luak - Siti Khairun Nisa; Wiwik Gusnita; Juliana Siregar; Cici Andriani (Universitas Negeri Padang, 2025)
The purpose of the study was to describe; (1) the learning motivation of class XI students at SMK Negeri 1, Luak District, (2) the learning independence of class XI students at SMK Negeri 1, Luak District, (3) the relationship between learning motivation and learning independence of class XI students at SMK Negeri 1, Luak District. This type of research is quantitative with a correlational approach. The population of the study was 224 students, with a sample of 143 students of grade XI at SMK Negeri 1, Luak District consisting of 9 classrooms. The research instrument was a questionnaire on student learning motivation and learning independence with a Likert model scale. The data was processed using data description analysis, normality test, linearity, correlation and t-test. The results of the study showed that (1) the learning motivation of class XI students of SMK Negeri 1 Luak District as a whole from 143 respondents was known to have the highest percentage at the